Supervisory Management: The Art of Inspiring, Empowering, and Developing, 10th Edition - Donald C. Mosley; Donald C. Mosley, Jr.; Paul H. Pietri (Cengage Learning, 2018)
SUPERVISORY MANAGEMENT inspires students--emphasizing the positive approach of working cooperatively WITH people to develop and empower them to better perform in their working roles. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.